2021
DOI: 10.3389/fimmu.2021.580271
|View full text |Cite
|
Sign up to set email alerts
|

Renal Involvement and HBV Infection Are Common in Chinese Patients With Cryoglobulinemia

Abstract: Objectives: This study aimed to describe the main characteristics of Chinese patients with cryoglobulinemia, especially the characteristics of patients with different causes of cryoglobulinemia.Methods: Eighty inpatients diagnosed with cryoglobulinemia from different wards in Peking Union Medical College Hospital were included in this study. Demographic, clinical, biological, and renal pathological data were collected. We analyzed the characteristics of 61 patients with different causes of cryoglobulinemia.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Other biological features include cryoglobulin type, anaemia, thrombocytopenia, leukopenia, hypocomplementaemia, hyperglobulinaemia and rheumatoid factor positivity. 7 Cryoglobulinaemia can manifest as fatigue, purpura, and joint pain, and can involve the kidneys and peripheral nervous system. 8 Type II and mixed cryoglobulinaemia are seen mainly in HCV infections and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other biological features include cryoglobulin type, anaemia, thrombocytopenia, leukopenia, hypocomplementaemia, hyperglobulinaemia and rheumatoid factor positivity. 7 Cryoglobulinaemia can manifest as fatigue, purpura, and joint pain, and can involve the kidneys and peripheral nervous system. 8 Type II and mixed cryoglobulinaemia are seen mainly in HCV infections and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Studies at different centres in China have focused on HBV-associated cryoglobulinaemia, 13 , 14 especially cases with renal involvement. 7 Some research has reported that the HBV-infection rate in patients with cryoglobulinaemia may be equal to or greater than the HCV-infection rate. 15 Antiviral nucleoside analogues, including entecavir, adefovir dipivoxil and lamivudine, are safe and effective for treating patients with HBV-associated cryoglobulinaemia vasculitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies from Europe (mainly France and Italy), cryoVas can develop in 1%-4% of patients with HBV infection (48)(49)(50)(51)(52)(53). HBV infection might be more common in Chinese patients with cryoglobulinemia (54). The presentation of HBV-associated Cry-oVas had no peculiarity, and patients showed purpura (100%), arthralgia (71%), peripheral neuropathy (29%), GN (18%), and MC type 2/type 3 (88%/12%) (49).…”
Section: Mixed Cryoglobulinemia Vasculitismentioning
confidence: 99%
“…Recently, several reports from China showed that renal involvement and HBV infection were common in Chinese patients with cryoglobulinemia (70,71). Although HBV-associated GN decreased over the past decade thanks to HBV vaccine campaign, it remains an important issue in endemic countries for HBV infection as China (72).…”
Section: Renal Manifestationsmentioning
confidence: 99%